The darkest white : a mountain legend and the avalanche that took him - Blehm, Eric (HarperCollins Publishers, 2024)
"From Eric Blehm, the bestselling author of The Last Season and Fearless, comes an extraordinary new book in the vein of Into the Wild, the story of the legendary snowboarder Craig Kelly and his death in the 2003 Durrand Glacier Avalanche-a devastating and controversial tragedy that claimed the lives of seven people. On January 20, 2003, a thunderous crack rang out and a 100-foot-wide tide of snow barreled down the Northern Selkirk Mountains in British Columbia, Canada. More than a dozen skiers and snowboarders were thrust down the mountain, buried beneath several tons of rock-hard snow and ice in the Durrand Glacier Avalanche. A heroic search and rescue ensued. Among those buried was Craig Kelly-"the Michael Jordan of snowboarding"-a man who had propelled the sport into the mainstream before walking away from competitions, to rekindle his passion in the untamed alpine wilds of North America The Darkest White is the story of Craig Kelly's life, a heartbreaking but extraordinary and inspiring odyssey of a latchkey kid whose athletic prowess and innovations would revolutionize winter sports, take him around the globe, and push him into ever more extreme environments that would ultimately take his life. It is also a definitive, immersive account of snowboarding and the cultural movement that exploded around it, growing the sport from minor Gen X cult hobby to Olympic centerpiece and a billion-dollar business full of feuds and rivalries. Finally, The Darkest White is a mesmerizing, cautionary portrait of the mountains, of the allure and the glory they offer, and of the avalanches they unleash with unforgiving fury"--